The Role of Information and Communication Technology in Implementing a Learning Organization Strategy - Dahou, Khadra . B .; Al-adaileh, Raid Mohâ€™d; Hacini, Ishaq . L . (Mediterranean Journal of Social Sciences, 2012)
The aggregative aim orienting this research was to examine the impact of the information and communication technology(ICT) on the success of the implementation of a learning organization (LO) strategy. From 416 questionnaires, conducted within thestrategic Algerian state-owned company: Sonatrach, results indicated that ICT have a significant positive statistical influence on thesuccess of the implementation of the â€œLearning Sonatrachâ€ strategy.The research provides concrete evidence of the consciousness ofthe Algerian managers of the importance of transforming their organizations into learning systems and the necessity of fostering up-todatetechnologies that would facilitate the transformation process. The study revealed a number of recommendations for academicresearchers and managers.